Odorant receptor phylogeny confirms conserved channels for sex pheromone and host plant signals in tortricid moths. Issue 14 (30th June 2020) - Gonzalez, Francisco; Borrero‐Echeverry, Felipe; Jósvai, Júlia K.; Strandh, Maria; Unelius, C. Rikard; Tóth, Miklós; Witzgall, Peter; Bengtsson, Marie; Walker, William B.
Abstract: The search for mates and food is mediated by volatile chemicals. Insects sense food odorants and sex pheromones through odorant receptors (ORs) and pheromone receptors (PRs), which are expressed in olfactory sensory neurons. Molecular phylogenetics of ORs, informed by behavioral and functional data, generates sound hypotheses for the identification of semiochemicals driving olfactory behavior. Studying orthologous receptors and their ligands across taxa affords insights into the role of chemical communication in reproductive isolation and phylogenetic divergence. The female sex pheromone of green budworm moth Hedya nubiferana (Lepidoptera, Totricidae) is a blend of two unsaturated acetates, only a blend of both elicits male attraction. Females produce in addition codlemone, which is the sex pheromone of another tortricid, codling moth Cydia pomonella . Codlemone also attracts green budworm moth males. Concomitantly, green budworm and codling moth males are attracted to the host plant volatile pear ester. A congruent behavioral response to the same pheromone and plant volatile in two tortricid species suggests co‐occurrence of dedicated olfactory channels. In codling moth, one PR is tuned to both compounds, the sex pheromone codlemone and the plant volatile pear ester. Our phylogenetic analysis finds that green budworm moth expresses an orthologous PR gene. Shared ancestry, and high levels of amino acid identity and sequence similarity, in codling and green budworm moth PRs offer an explanation for parallel attraction of both species to the same compounds. A conserved olfactory channel for a sex pheromone and a host plant volatile substantiates the alliance of social and habitat signals in insect chemical communication. Field attraction assays confirm that in silico investigations of ORs afford powerful predictions for an efficient identification of behavior‐modifying semiochemicals, for an improved understanding of the mechanisms of host plant attraction in insect herbivores and for the further development of sustainable insect control. Abstract : Hedya nubiferana (a tortricid moth on apple and other rosacean plants) is attracted to the sex pheromone and to the plant‐derived kairomone of codling moth (another tortricid moth feeding on apple). A conserved odorant receptor is the basis for this coincidence, which demonstrates the interaction of social signals and food cues in insect herbivores.